A personalized method of cloud manufacturing service customization. Issue 4 (3rd April 2021) - Huo, Yunliang; Xiong, Ji; You, Qianbing; Guo, Zhixing; Xiang, Hai
ABSTRACT: In order to provide consumers with personalized cloud manufacturing services, and to form a crowd-sourcing cloud alliance for Small and Medium enterprises (SMEs), a cloud personalized method based on the Evolutionary Game Algorithm (EGA) was proposed in this paper. First, the cloud services were accurately described from two aspects (the enterprise and resources). Besides, an optimization model was established to obtain cloud alliance which can achieve personalized service customization based on consumer preferences. Furthermore, Evolutionary Game algorithm (EGA) which is skilled at combination optimization, was adopted to solve the proposed model. Finally, experiments were designed to verify the feasibility and efficiency of the method, and the results shown that the proposed method is not only feasible, but has much greater efficiency than existing evolutionary methods.